Identification of Individual Neurons Reflecting Short- and Long-Term Visual Memory in an Arthropod - Berón de Astrada, Martín (2013)
Background: Due to the complexity and variability of natural environments, the ability to adaptively modify behavior is of fundamental biological importance. Motion vision provides essential cues for guiding critical behaviors such as prey, predator, or mate detection. However, when confronted with the repeated sight of a moving object that turns out to be irrel- evant, most animals will learn to ignore it. The neural mecha- nisms by which moving objects can be ignored are unknown. Although many arthropods exhibit behavioral adaptation to re- petitive moving objects, the underlying neural mechanisms have been difficult to study, due to the difficulty of recording activity from the small columnar neurons in peripheral motion detection circuits. Results: We developed an experimental approach in an arthropod to record the calcium responses of visual neurons in vivo. We show that peripheral columnar neurons that convey visual information into the second optic neuropil persist in responding to the repeated presentation of an innocuous moving object. However, activity in the columnar neurons that convey the visual information from the second to the third optic neuropil is suppressed during high-frequency stimulus repetitions. In accordance with the animal’s behavioral changes, the suppression of neural activity is fast but short lasting and restricted to the retina’s trained area. Conclusions: Columnar neurons from the second optic neuro- pil are likely the main plastic locus responsible for the modifi- cations in animal behavior when confronted with rapidly repeated object motion. Our results demonstrate that visually guided behaviors can be determined by neural plasticity that occurs surprisingly early in the visual pathway.